2022
DOI: 10.1021/acsmedchemlett.2c00327
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Study of Tertiary Alcohol Hsp90α-Selective Inhibitors with Novel Binding Mode

Abstract: The heat shock protein 90 (Hsp90) family of molecular chaperones mediates the folding and activation of client proteins associated with all 10 hallmarks of cancer. Herein, the design, synthesis, and biological validation of Hsp90α-selective inhibitors that contain a tertiary alcohol are reported. Forty-one analogues were synthesized to modulate hydrogen-bonding interactions and to probe for steric and hydrophobic interactions within the Hsp90α binding site. Cocrystal structures of lead compound 23d (IC50 = 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Prior studies demonstrated that the introduction of a fluorine onto the solvent-exposed isoindoline in KUNA-111 had no effect on the affinity or selectivity for Hsp90α. 8 Therefore, the goal of this study was to attach a permanently charged moiety to the KUNA-115 scaffold at this location. It was hypothesized that the permanent charge would prevent the inhibitor from crossing the cellular membrane without drastically affecting affinity or selectivity, as the isoindoline is directed toward the solvent-exposed portion of the binding site (Figure 2).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies demonstrated that the introduction of a fluorine onto the solvent-exposed isoindoline in KUNA-111 had no effect on the affinity or selectivity for Hsp90α. 8 Therefore, the goal of this study was to attach a permanently charged moiety to the KUNA-115 scaffold at this location. It was hypothesized that the permanent charge would prevent the inhibitor from crossing the cellular membrane without drastically affecting affinity or selectivity, as the isoindoline is directed toward the solvent-exposed portion of the binding site (Figure 2).…”
mentioning
confidence: 99%
“…As an alternative strategy, Hsp90-isoform-selective inhibitors have been developed for all four isoforms to avoid complications associated with pan-inhibition. Despite their distinct cellular localization, function, and client proteins, all four isoforms share highly conserved structures. Hsp90α and Hsp90β reside in the cytosol, whereas glucose-regulated protein 94 (Grp94) is localized to the endoplasmic reticulum and tumor necrosis factor receptor-associated protein 1 (Trap1) resides in the mitochondria.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, most of these molecules failed due to cardiac and ocular toxicities, as well as dose-escalating toxicities, associated with pan -inhibition of all four Hsp90 isoforms that results in induction of the pro-survival heat shock response (HSR), which includes the overexpression of Hsp90. , Therefore, a need exists for inhibitors that can provide an alternative mechanism of action. Several approaches are currently being explored to minimize the deleterious consequences that result from pan -Hsp90 inhibition and include C-terminal inhibition, disruption of Hsp90 C-terminal dimerization, isoform-selective inhibition, and disruption of Hsp90 protein–protein interactions (PPIs) between client substrates and/or cochaperones …”
mentioning
confidence: 99%